Secularization and the Future of Religion - Bukevičiūtė, Aistė (Problemos, 2007)
[full article and abstract in Lithuanian; abstract in English] The article analyses the problem of the definition of secularisation and its impact on our worldview. The influence of the processes of secularisation on the revival of religion is discussed. While proposing that the concept of secularisation is related to the definition of religion, the article tries to show that a definition of religion that is too broad can give rise to a situation in which ideologies are treated as religions. If we consider secularisation as one of the main features of religious dynamics, it is obvious that rather than being a one-way process leading to the vanishing of religion, it is one that encourages the rise of new religions or else the transformation of old ones.